Porcine FcγRIIb mediates enhancement of porcine reproductive and respiratory syndrome virus (PRRSV) infection. - Songlin Qiao (Public Library of Science (PLoS), 2011)
Antibody-dependent enhancement (ADE) of virus infection caused by the uptake of virus-antibody complexes by FcγRs is a significant obstacle to the development of effective vaccines to control certain human and animal viral diseases. The activation FcγRs, including FcγRI and FcγRIIa have been shown to mediate ADE infection of virus. In the present paper, we showed that pocine FcγRIIb, an inhibitory FcγR, mediates ADE of PRRSV infection. Stable Marc-145 cell lines expressing poFcγRIIb (Marc-poFcγRII) were established. The relative yield of progeny virus was significantly increased in the presence of sub-neutralization anti-PRRSV antibody. The Fab fragment and normal porcine sera had no effect. Anti-poFcγRII antibody inhibited the enhancement of infection when cells were infected in the presence of anti-PRRSV antibody, but not when cells were infected in the absence of antibody. These results indicate that enhancement of infection in these cells by anti-PRRSV virus antibody is FcγRII-mediated. Identification of the inhibitory FcγR mediating ADE infection should expand our understanding of the mechanisms of pathogenesis for a broad range of infectious diseases and may open many approaches for improvements to the treatment and prevention of such diseases.